The Role of Culturally Responsive Teaching in Developing Students’ Self-Regulated Learning in Elementary School Mathematics Education: A Systematic Literature Review - Amelia Dwi Astuti; Achmad Zainul Rozikin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Background: Self-Regulated Learning is one of the key factors that contributes to students’ success in elementary mathematics education. However, numerous studies have indicated that students’ self-regulation skills still require further enhancement through learning experiences that are aligned with their characteristics and learning backgrounds. One pedagogical approach that has the potential to support the development of Self-Regulated Learning is Culturally Responsive Teaching, an instructional approach that integrates students’ cultural backgrounds into the teaching and learning process. Aim: This study aims to examine the role of Culturally Responsive Teaching in fostering students’ Self-Regulated Learning in elementary school mathematics education through a Systematic Literature Review approach. Data were collected from articles indexed in the Google Scholar and ERIC databases. The data were analyzed using a thematic synthesis technique to identify patterns of Culturally Responsive Teaching implementation and its contribution to the development of students’ Self-Regulated Learning. Result and Discussions: The findings reveal that the implementation of Culturally Responsive Teaching in elementary mathematics education is generally carried out through the integration of local culture, ethnomathematics, the use of students’ real-life contexts, and the creation of inclusive learning environments that value cultural diversity. These practices contribute to the enhancement of intrinsic motivation, self-efficacy, learning engagement, goal-setting skills, self-monitoring, and self-reflection, which are essential components of Self-Regulated Learning. Conclusion: Therefore, Culturally Responsive Teaching can serve as an effective pedagogical approach to promoting students’ autonomous learning while fostering mathematics instruction that is more meaningful, contextualized, and responsive to cultural diversity.